Sustainable synthesis of zinc oxide nanoparticles using Terminalia chebula extract: Effect of concentration and temperature on properties and antibacterial efficacy - Akhter, Syed Md Humayun; Siddiqui, Vasi Uddin; Ahmad, Shameem; Husain, Dilawar; Naeem, Sajid; Alam, Md Tanwir (Elsevier, 2024)
Nanotechnology has revolutionized various fields, offering promising applications in medicine, catalysis, electronics and environmental remediation. One of the key challenges in nanoparticle synthesis is the development of environmentally friendly methods. A fruit extract of Terminalia chebula was used to make zinc oxide nanoparticles (ZnONPs), which were then annealed at temperatures ranging from 400 to 800 °C. The structural and optical properties of the annealed zinc oxide nanoparticles were investigated using different characterization techniques, such as FTIR, XRD, UV–visible spectroscopy, HR-TEM, SEM and EDX. The crystallinity, shape and size of the as-prepared ZnONPs showed a change when the annealing temperature was increased to 800 °C. A small red shift in the UV–vis absorption spectra was clearly observed with an increase in the annealing temperature. The antibacterial activity of the as-synthesised annealed ZnONPs was further tested against Salmonella enterica, Staphylococcus aureus and Escherichia coli. The antibacterial properties of the as-synthesised ZnONPs were synergistic. Formulation of ZnONPs at 400 and 600 °C showed the most effective antibacterial activity against gram negative strains. © 2024 Elsevier B.V.